A Gustavite-Cosalite-Galena_bearing Mineral Suite from the Cryolite Deposit at Ivigtut, South Greenland. - Karup-Møller, S. (Meddelelser om Grønland, 1973)
A suite of rare bismuth-lead-silver-copper sulphides associated with various gangue minerals was found in the cryolite deposit. The mineral suite occurred close to the contact between the siderite- and fluorspar-zones. It was exposed over an area about half a meter in diameter and is characterized by sulphide-disseminated topaz-fluorspar material contained in a mixture of fluorspar, weberite, fine grained muscovite and very minor amounts of quartz, referred to as "the matrix gangue minerals". The sulphides present are gustavite (with an exsolved mineral referred to as phase X), cosalite and galena associated with some aikinite, berryite and pyrite. Matildite, argentite( ?), gold, bismuth, chalcopyrite, sphalerite, pyrrhotite, marcasite and a new mineral earlier described as "Mineral A" are present in very minor amounts. Rare grains of coffinite sometimes with a core of a sulphide-uraninite intergrowth are also present. Data on gustavite, phase X, berryite and mineral A have already been published; the properties of the other minerals present and their relationships are described. Investigations of fluids entrapped in fluorspar indicates a maximum temperature of formations of the sulphides around 300° C. The minimum temperature of formation may lie around 200° C. The mineral suite is concluded to have crystallized from fluids without introduction of additional material as the crystallization took place. The fluids may possibly have been present as a low temperature sulphide melt. The crystallization sequence of the mineral suite and the possible changes in the composition of the fluids as the crystallization progressed are discussed. The mineralizing fluids may have developed from mobilization of silver-bismuthbearing galena which constitutes slightly less than half a percent of the cryolitesiderite ore zone of the cryolite deposit. This mobilization took place when late fluorspar-zone material reacted with galena-disseminated siderite-rich material.